Identifying and supporting children with specific learning difficulties : looking beyond the label to assess the whole child - Macintyre, Christine, 1938- (RoutledgeFalmer, 2003)
By highlighting the myriad of over-laps between learning difficulties, as well as questioning many assumptions about certain conditions, the authors of this book take a uniquely holistic angle on inclusive education.